The Survival of Sharia Islamic Divorce Law in the Syrian and Egyptian Personal Status Laws - Alkhaled, Mohamad (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The family law was not codified in both Syria and Egypt until 1917 when the Ottomans issued the Ottoman Family Rights Law, which applied to Muslims, Christians, and Jews each according to its provisions. This Ottoman Family Rights Law and the book of the Egyptian scholar Muhammad Qadri Pasha (‘Legal Ruling on Personal Status’) formed the first core of personal status laws in both Egypt and Syria, which s explains the survival of Islamic law to this day in personal status laws, in contrast to other branches of law. This paper presents a comparative study between the Egyptian Personal Status Law No. 25 of 1920, and the Syrian Personal Status Law No. 59 of 1953, regarding divorce provisions.